Voltage-dependent anion channel 1 oligomerization regulates PANoptosis in retinal ischemia–reperfusion injury - Hao Wan; Xiaoxia Ban; Ye He; Yandi Yang; Ximin Hu; Lei Shang; Xinxing Wan; Qi Zhang; Kun Xiong (Neural Regeneration Research)
Ischemia–reperfusion injury is a common pathophysiological mechanism in retinal degeneration. PANoptosis is a newly defined integral form of regulated cell death that combines the key features of pyroptosis, apoptosis, and necroptosis. Oligomerization of mitochondrial voltage-dependent anion channel 1 is an important pathological event in regulating cell death in retinal ischemia–reperfusion injury. However, its role in PANoptosis remains largely unknown. In this study, we demonstrated that voltage-dependent anion channel 1 oligomerization-mediated mitochondrial dysfunction was associated with PANoptosis in retinal ischemia–reperfusion injury. Inhibition of voltage-dependent anion channel 1 oligomerization suppressed mitochondrial dysfunction and PANoptosis in retinal cells subjected to ischemia–reperfusion injury. Mechanistically, mitochondria-derived reactive oxygen species played a central role in the voltage-dependent anion channel 1-mediated regulation of PANoptosis by promoting PANoptosome assembly. Moreover, inhibiting voltage-dependent anion channel 1 oligomerization protected against PANoptosis in the retinas of rats subjected to ischemia–reperfusion injury. Overall, our findings reveal the critical role of voltage-dependent anion channel 1 oligomerization in regulating PANoptosis in retinal ischemia–reperfusion injury, highlighting voltage-dependent anion channel 1 as a promising therapeutic target.